Neurally Adjusted Ventilator Assist in Infants With Acute Respiratory Failure: A Literature Scoping Review. Issue 10 (13th April 2021) - Harris, Julia; Tibby, Shane M; Endacott, Ruth; Latour, Jos M.
Abstract : Supplemental Digital Content is available in the text. Abstract : OBJECTIVES: To map the evidence for neurally adjusted ventilatory assist strategies, outcome measures, and sedation practices in infants less than 12 months with acute respiratory failure using the Preferred Reporting Items for Systematic Reviews and Meta-Analyses Extension for Scoping Reviews guidance. DATA SOURCES: CINAHL, MEDLINE, COCHRANE, JBI, EMBASE, PsycINFO, Google scholar, BNI, AMED. Trial registers included the following: ClinicalTrials.gov, European Union clinical trials register, International Standardized Randomized Controlled Trial Number register. Also included were Ethos, Grey literature, Google, dissertation abstracts, EMBASE conference proceedings. STUDY SELECTION: Abstracts were screened followed by review of full text. Articles incorporating a heterogeneous population of both infants and older children were assessed, and where possible, data for infants were extracted. Fifteen articles were included. Ten articles were primary research: randomized controlled trial ( n = 3), cohort studies ( n = 4), retrospective data analysis ( n = 2), case series ( n = 1). Other articles are expert opinion ( n = 2), neurally adjusted ventilatory assist updates ( n = 1), and a literature review ( n = 2). Three studies included exclusively infants. We also included 12 studies reporting jointly on infants and children. DATA EXTRACTION: A standardized data extraction tool was used. DATA SYNTHESIS: Key findings were that evidence related to neurally adjusted ventilatory assist ventilation strategies in infants and related to specific primary conditions is limited. The setting of neurally adjusted ventilatory assist level is not consistent, and how to optimize this mode of ventilation was not documented. Outcome measures varied considerably, most studies focused on improvements in respiratory and physiological variables. Sedation use is variable with regard to medication type and dose. There is an indication that less sedation is required in patients receiving neurally adjusted ventilatory assist, but no conclusive evidence to support this. CONCLUSIONS: This review highlights a lack of standardized strategies for neurally adjusted ventilatory assist ventilation and sedation practices among infants with acute respiratory failure. Studies were limited by small sample sizes and a lack of focus on specific patient groups. Robust studies are needed to provide evidence-based clinical recommendations for the use of neurally adjusted ventilatory assist in infants with acute respiratory failure.